Parental Influence on Young Children's Physical Activity - Cheryl A. Zecevic; Line Tremblay; Tanya Lovsin; Lariviere Michel (International Journal of Pediatrics)
Parents influence on their young children's physical activity (PA) behaviours was examined in a sample of 102 preschool-aged children (54 boys). Questionnaires regarding family sociodemographics and physical activity habits were completed. Results showed that children who received greater parental support for activity (B=.78, P<.10) and had parents who rated PA as highly enjoyable (B=.69, P<.05) were significantly more likely to engage in one hour or more of daily PA. Being an older child (B=−.08, P<.01), having older parents (B=−.26, P<.01), and watching more than one hour of television/videos per day (B=1.55, P<.01) reduced the likelihood that a child would be rated as highly active. Children who received greater parental support for PA were 6.3 times more likely to be highly active than inactive (B=1.44, P<.05). Thus, parents can promote PA among their preschoolers, not only by limiting TV time but also by being highly supportive of their children's active pursuits.